Contribution of vascular risk factors to the progression in Alzheimer disease. - Helzner, Elizabeth P; Luchsinger, José A; Scarmeas, Nikolaos; Cosentino, Stephanie; Brickman, Adam M; Glymour, M Maria; Stern, Yaakov (Arch Neurol, 2009)
BACKGROUND: Vascular factors including medical history (heart disease, stroke, diabetes, and hypertension), smoking, and prediagnosis blood lipid measurements (cholesterol: total, high-density lipoprotein, low-density lipoprotein [LDL-C], and triglyceride concentrations) may be predictors for progression of Alzheimer disease (AD). OBJECTIVE: To determine whether prediagnosis vascular risk factors are associated with progression of AD. DESIGN: Inception cohort followed up longitudinally for a mean of 3.5 (up to 10.2) years. SETTING: Washington Heights/Inwood Columbia Aging Project, New York, New York. Patients One hundred fifty-six patients with incident AD (mean age at diagnosis, 83 years). Main Outcome Measure Change in a composite score of cognitive ability from diagnosis onward. RESULTS: In generalized estimating equation models (adjusted for age, race/ethnicity, and years of education), higher cholesterol (total cholesterol and LDL-C) concentrations and history of diabetes were associated with faster cognitive decline. Each 10-U increase in cholesterol and LDL-C was associated with a 0.10-SD decrease in cognitive score per year of follow-up (P < .001 for total cholesterol; P = .001 for LDL-C). High-density lipoprotein cholesterol and triglyceride concentrations were not associated with rate of decline. A history of diabetes was associated with an additional 0.05-SD decrease in cognitive score per year (P = .05). History of heart disease and stroke were associated with cognitive decline only in carriers of the apolipoprotein E epsilon4 (APOE-epsilon4) gene. In a final generalized estimating equation model that included high-density lipoprotein cholesterol and LDL-C concentrations and history of diabetes, only higher LDL-C was independently associated with faster cognitive decline. CONCLUSION: Higher prediagnosis total cholesterol and LDL-C concentrations and history of diabetes were associated with faster cognitive decline in patients with incident AD, which provides further evidence for the role of vascular risk factors in the course of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cerebrovascular Disorders; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Cognition; Cohort Studies; Community Health Planning; Disease Progression; Female; Humans; Male; Models, Statistical; Predictive Value of Tests; Risk Factors